Effects of pre-treatments on banana leaf as packaging material for baye-baye - Negrillo, Salve Lyan Cordevilla (2010.)
The effectiveness of pre-treatment employed on banana leaf was investigated by monitoring changes of physico-chemical and sensorial properties of banana leaf and packed baye-baye until 72 hours.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Banana leaf; Baye-baye.